Vernacular Security and Religion in Tunisia: The Role of Local Imams in the Implementation of Preventing Violent Extremism Measures - Cuccu, Fabrizio Leonardo (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
In Tunisia, the 2016 national strategy against terrorism introduced the concept of preventive measures, which legitimized tighter state control over religious discourses and practices. To bring a local perspective to the study of international preventative measures, I build upon the concept of “vernacular security” to examine how Tunisian imams involved in preventing violent extremism (PVE) programs understand security, violent extremism, radicalization, and their role as non-traditional security actors. To achieve this, I observe how imams describe their own experiences of security, in their own words and through their own understandings. Through ethnographic interviews conducted with local imams between 2019 and 2020, this research focuses on the way in which they perceive, re-enact, and influence security practices, with a particular focus on the relationship between religion and security, a central subject in post-revolutionary Tunisia. In so doing, this paper argues that local imams involved in PVE programs reproduce local and global security discourses, while at the same challenging their role in community policing.